The Use of ICT in Education: Focus on Nigeria - Oye, N. D.; ., M. A. Shakil (Information Management and Business Review, 2011)
The use of ICT in educational settings is a catalyst for change. The paper has sought to explore the role of ICT in education as we progress into the 21st century. The first phase focuses on the conceptual framework of the use of ICT in education. In this model the dependent variable is education and its sub variables are educational level of teachers and students which is directly affected by the independent variables which are the use of ICTs, ICT infrastructure and staff development. The second phase is the pilot study to answer two major questions: (i) Is ICT mandatory or voluntary at your institutions? (ii) What are the greatest barriers to using ICT to you as an academician? The results show that majority of the academic staff (86%) responded that ICT is mandatory. However, the survey revealed that most of the part-time lecturers ticked the use of ICT as voluntary. Some of these part-time lecturers in the cadre of professors, responded to Q32 as (do not fit my program). Actually in their dispensation, lecturing was done using the chalk board only. The research confirms that two major barriers affect the use of ICT; they are lack of time to use ICT the systems and training opportunities. Respondents on these are 38% and 32% respectively. Based on these findings, the paper recommended that, all employed teachers in Federal, State and Private institutions should undertake mandatory training and retraining on ICT programmers. The government should develop ICT policies and guidelines for the application of ICT in education.